2016
DOI: 10.1134/s1061934816110113
|View full text |Cite
|
Sign up to set email alerts
|

A gas chromatographic study of the residual contents of a medieval sphero-conical vessel

Abstract: Black deposit was discovered on the inner wall of a sphero-conical vessel found during archaeological excavations on the territory of the Volga Bulgars. Compounds from the deposit were extracted with organic solvents and studied by gas chromatography with flame ionization and mass spectrometry detectors. Abietic acid derivatives, including retene, present in the composition of soft wood turpentine were identified. The relatively high retene concentration in the remains of the spherocone and also the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In the chromatograms of extracts from the ceramic surface with traces of resin coating, normal hydrocarbons C 20 -C 35 were not detected. This made it possible to exclude the presence of petroleum products in the resin coating, as well as beeswax and vegetable wax [6,7]. Methyl esters of fatty acids, biomarkers of ani- Relative intensity 1000 mal fats and vegetable oils, were also absent, which made it possible to exclude the use of the studied ceramic vessels for the preparation and storage of animal and plant food [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…In the chromatograms of extracts from the ceramic surface with traces of resin coating, normal hydrocarbons C 20 -C 35 were not detected. This made it possible to exclude the presence of petroleum products in the resin coating, as well as beeswax and vegetable wax [6,7]. Methyl esters of fatty acids, biomarkers of ani- Relative intensity 1000 mal fats and vegetable oils, were also absent, which made it possible to exclude the use of the studied ceramic vessels for the preparation and storage of animal and plant food [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…The simple utilitarian uses based on their size, weight and shape include a plumb bob [ 1 ], a loom weight and an architectural feature [ 9 ]. If considered a vessel the proposed uses include liquid sprinkler [ 9 ], fire starter [ 10 , 11 ], fire blower [ 12 ], aeolipile [ 9 , 12 14 ], lamp [ 4 , 15 ], smoking pipe [ 7 , 16 ], alchemical vessel [ 7 , 13 , 16 , 17 ] or parts of a distillation apparatus [ 17 , 18 ]. From historical documents there is support for thick-walled vessels being used in warfare as grenades [ 9 , 12 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Brosh [ 10 ] on the contents of sphero-conical vessels of unknown provenance, identified iron and proposed this was from iron pyrite which could have served as a fire starter. A study on a sphero-conical vessel from Bolgar, Russia, identified resin acids, initially interpreted as part of distillation apparatus [ 18 ], later reinterpreted as a medicinal kit [ 21 ]. Finally, fats and oils were characterised on sphero-conical vessels from Armenia that were proposed to be perfume or medicinal containers [ 27 ].…”
Section: Introductionmentioning
confidence: 99%